Particulate‐Based Single‐Dose Local Immunosuppressive Regimen for Inducing Tolerogenic Dendritic Cells in Xenogeneic Islet Transplantation. Issue 2 (29th November 2020) - Pathak, Shiva; Acharya, Suman; Regmi, Shobha; Shrestha, Prakash; You, Zhiwei; Bae, Young Kyung; Park, Min Hui; Yook, Simmyung; Kim, Jae‐Ryong; Park, So Young; Jeong, Daewon; Yong, Chul Soon; et al.
Abstract: Recent studies emphasize on developing immune tolerance by an interim administration of various immunosuppressive drugs. In this study, a robust protocol is reported for local immunomodulation using a single‐dose of FK506 microspheres and clodronate liposomes (mFK+CLO) in a xenogeneic model of islet transplantation. Surprisingly, the single‐dose treatment with mFK+CLO induce tolerance to the islet xenograft. The recipient mice display tolerogenic dendritic cells (tDCs) with decreased antigen presenting ability and T cell activation capacity. Furthermore, a reduced percentage of CD4 + and CD8 + T cells and an impaired differentiation of naïve CD4 + T cells into interferon‐ γ producing Th1 and interleukin‐17 producing Th17 cells are observed. In addition, the immunosuppressive protocol leads to the generation of Foxp3 + regulatory T cells (Tregs) which are required for the long‐term graft survival. The enhanced generation of tDCs and Tregs by the single treatment of mFK+CLO cause xenograft tolerance, suggesting a possible clinical strategy which may pave the way towards improving therapeutic outcomes of clinical islet transplantation. Abstract : In this study, a robust immunosuppressive regimen is developed for tolerance induction in a xenogeneic islet transplantation model. Single‐dose of locally‐delivered particulate‐based regimen leads to indefinite survival of the islets transplanted into subcutaneous space of immunocompetent diabetic mice. Mechanistically, the combination of FK506 microspheres and clodronate liposomes induces tolerogenic dendritic cells which are capable of generating graft‐protective regulatory T cells.